Aircraft measurements of wind and temperature during flight P5_232_HALO_2022_2204011201 of the HALO-AC3 campaign in 2022 - Lüpkes, Christof; Hartmann, Jörg; Michaelis, Janosch; Herber, Andreas (In: Lüpkes, C et al. (2024): Aircraft measurements of wind and temperature during the HALO-AC3 campaign in 2022 [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.968911, 2024)
During the HALO-AC3 campaign conducted in March and April 2022 in Svalbard meteorological data (temperature, 3 wind components, air pressure) have been measured in high temporal resolution (100 Hz) using instrumentation that was installed at the nosebooms of Polar 5 and Polar 6. For each flight the data are given as functions of time and position (including height above ground) along the flight tracks. All flights started and ended in Longyearbyen, Svalbard. Each file represents an entire flight starting well before the first movement of the plane and ending after the final parking position has been reached after landing. The wind measurement is only valid during flight and the full accuracy is only achieved during straight level flight sections. The absolute accuracy of the wind components is 0.5m/s for straight and level flights sections and the relative accuracy of the vertical wind speed is about 0.15m/s for straight and level flight sections. For these sections, which can be obtained on the basis of the given roll and pitch angles of the aircraft, the 100 Hz data can be used to derive turbulent fluxes of momentum and sensible heat. For further informations on the data processing and accuracy of the turbulence measurement refer to Hartmann et al. (2018, doi:10.5194/amt-11-4567-2018). The current dataset represents a downsampled version of 100Hz data to 1Hz by a moving average filter. On several occasions wind data are not available due to icing of the sensors. For those instances wind data are set to zero.